2020
DOI: 10.3390/antibiotics9030105
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antivirulence Activity of Glucocorticoid PYED-1 against Stenotrophomonas maltophilia

Abstract: Stenotrophomonas maltophilia, an environmental Gram-negative bacterium, is an emerging nosocomial opportunistic pathogen that causes life-threatening infections in immunocompromised patients and chronic pulmonary infections in cystic fibrosis patients. Due to increasing resistance to multiple classes of antibiotics, S. maltophilia infections are difficult to treat successfully. This makes the search for new antimicrobial strategies mandatory. In this study, the antibacterial activity of the heterocyclic cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…The time-kill curve analysis against S. aureus demonstrated a concentration-dependent rapid bactericidal activity of PYED-1 (Figure 4). In line with this, we have previously shown that PYED-1 exhibited bactericidal activity against S. maltophilia, and that the permeabilization of the bacterial membrane might contribute to the effect [7]. Our study demonstrated additivity of PYED-1/gentamicin and PYED-1/oxacillin combinations by checkerboard assay.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The time-kill curve analysis against S. aureus demonstrated a concentration-dependent rapid bactericidal activity of PYED-1 (Figure 4). In line with this, we have previously shown that PYED-1 exhibited bactericidal activity against S. maltophilia, and that the permeabilization of the bacterial membrane might contribute to the effect [7]. Our study demonstrated additivity of PYED-1/gentamicin and PYED-1/oxacillin combinations by checkerboard assay.…”
Section: Discussionsupporting
confidence: 88%
“…PYED-1 exerted a good inhibitory activity against E. faecalis, S. aureus, and A. baumannii, low to moderate activity against E. coli and P. aeruginosa, while it did not exert any appreciable inhibition against K. pneumoniae and E. aerogenes ( Tables 2 and 3). A weak effect was also observed in a previous report against S. maltophilia [7].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, PYED-1 at concentrations of up to 8 µg/mL did not impair planktonic growth at concentrations of up to 8 µg/mL (data not shown), thus suggesting that the reduction of biofilm formation caused by PYED-1 was due to its antibiofilm activity, and not to its antimicrobial activity. Similar results were obtained in previous studies on S. maltophilia [12], in which treatment with PYED-1 at 1/4× MIC, 1/8× MIC, and 1/16× MIC was able to inhibit biofilm formation by 97%, 90%, and 57%, respectively, compared with the untreated control. Biofilm formation was also assessed qualitatively using confocal laser scanning microscopy (CLSM).…”
Section: Effect Of Pyed-1 On S Aureus Biofilm Formationsupporting
confidence: 90%
“…In previous studies, we showed that pregnadiene-11-hydroxy-16α,17α-epoxy-3,20-dione-1 (PYED-1) exhibits effective antibacterial activity against S. aureus ATCC 29213 and A. baumannii ATCC 17978, without cytotoxic effects [10,11]. Additionally, we demonstrated that PYED-1 at sub-inhibitory concentrations hinders the biofilm formation of the Stenotrophomonas maltophilia K279a strain [12].…”
Section: Introductionmentioning
confidence: 90%